Ultrafast, low temperature microwave-assisted solvothermal synthesis of nanostructured lithium iron phosphate optimized by a chemometric approach. (1st December 2015) - Garino, N.; Bedini, A.; Chiappone, A.; Gerbaldi, C.
Graphical abstract: Highlights: Nanostructured LiFePO4 /C by microwave-assisted solvothermal synthesis. Novel, simple preparation at low temperature, with no critical parameters. Optimization by chemometric DoE approach demonstrated for the first time. Noticeable specific capacity and exceptional stability upon very long-term cycling. Improved long-term durability (> 1000 cycles) at 1C rate. Abstract: Nanostructured LiFePO4 /C composites having ordered olivine structure are prepared by a newly elaborated low temperature microwave-assisted solvothermal synthesis in the presence of a cationic surfactant. The microwave-assisted approach is simple and cost effective: it significantly decreases reaction times compared to the conventional hydrothermal/solvothermal processes. A study on the influence of the synthesis parameters on both the morphology and the electrochemical behavior of the samples is performed by means of X-ray powder diffraction, N2 physisorption at 77 K, scanning electron microscopy, cyclic voltammetry and constant current charge/discharge cycling. Moreover, a chemometric approach through design of experiments (DoE) is here successfully demonstrated for the first time for the optimization and fine tuning of the experimental conditions, including synthetic procedure and electrochemical characteristics of the materials. As a result, we show a nanostructured LiFePO4 /C with high rate capability and delivering a very stable cycling behavior for more than thousand cycles with excellent Coulombic efficiency and exceptional capacity retention at 1C.